Measuring productivity change in electricity generation management companies using DEA model and malmquist index - Mirza Hasan Hoseini (چشم‌انداز مدیریت صنعتی, 2012)
The present paper analyses the performance of the Iranian thermal power plant by working out the technical efficiency using the mathematical model of data envelopment Analysis (DEA). The DEA is a non linear programming way of calculating technical efficiency of the decision making units. This study use a Malmquist productivity index to investigate Total factor productivity (TFP) change for common set of Thermal power plants existing between 2002 and 2008 using prowess data base. The total factor productivity is decomposed into efficiency change (catching up phenomena) and technical change (innovations). The paper confirms the improvement in productivity, efficiency change and technical change of the Iranian thermal power plants from 2002 to 2008 and thus, help Tavaneer Company to monitor and diagnose changes in the productivity of its thermal power plants. Furthermore, the results allow the agents to define their efficiency profile as a function of their competitors and suggest to them some of the efficiency improvements that they should undertake. in the face of  the continuing liberalization of the Iranian power generation market Our analysis suggests that improvements in the efficiency and productivity of thermal power plant in iran have occurred, and there is a relationship between the restructuring and the enhancement of productivity.